A near-optimal green control for probabilistic routing protocols in delay-tolerant networks. (2017) - Ouadrhiri, Ahmed El; Kamili, Mohamed El; Rahmouni, Imane; Berrada, Ismail
Delay tolerant networks present a promising solution for environments where there is no continuous network connectivity. By using the store-carry and forward protocol, mobile nodes can communicate with each other even though there is no permanent link from the source to the destination. Since routing protocols in DTNs are based on mobile nodes for sending messages, the choice of the message forwarding strategy can have a major impact on the system performance. PRoPHET protocol is among the most widely used routing protocols for such networks. In this paper, we propose new energy efficient forwarding schemes for probabilistic routing protocols that can optimise different performance metrics. Based on some assumptions, we set new rules for message transmission to neighbouring nodes. Using the ONE simulator, numerical results show that our new forwarding schemes reduce the energy consumption considerably and deliver more messages compared to the original version of PRoPHET.